Two-dimensional C6X (X = P2, N2, NP) with ultra-wide bandgap and high carrier mobility - Xiaowei Chen; Renqun Li; Jiahe Lin; Qiubao Lin; Hongsheng He (Materials Research Express, 2023)
Two-dimensional (2D) materials with ultra-wide bandgap and high carrier mobility are highly promising for electronic applications. We predicted 2D C _3 P, C _3 N and C _6 NP monolayers through density-functional-theory calculations. The phonon spectra and Ab initio molecular dynamics simulation confirm that the three 2D materials exhibit good phase stability. The C _3 P monolayer shows excellent mechanical flexibility with a critical strain of 27%. The C _3 P and C _6 NP monolayers are ultra-wide bandgap semiconductors based on Heyd-Scuseria-Ernzerhof hybrid functional (HSE06) calculation. The C _3 P monolayer has a direct bandgap of 4.42 eV, and the C _6 NP and C _3 N monolayer have indirect bandgaps of 3.94 and 3.35 eV, respectively. The C _3 P monolayer exhibits a high hole mobility of 9.06 × 10 ^4 cm ^2 V ^−1 s ^−1 , and the C _3 N monolayer shows a high electron mobility of 4.52 × 10 ^4 cm ^2 V ^−1 s ^−1 . Hence, the C _3 P, C _3 N, and C _6 NP monolayers are promising materials for various electronic devices.